Strategi Pengembangan dan Implementasi Industri Pariwisata di Yogyakarta - Bagus Hendra Stia Pratama; Muhammad Tsani Aththoriq; Naerul Edwin Kiky Aprianto; Priska Ananda; Qothrotun Nada (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This study aims to analyze the strategies for developing the tourism industry in the Special Region of Yogyakarta, which is one of the main tourist destinations in Indonesia. The background of this research is based on the significant potential of the tourism sector to support regional economic growth through increased revenue from taxes and levies. However, the tourism industry in Yogyakarta faces various challenges, including global competition and changing tourist behaviors. Utilizing qualitative methods and Miles and Huberman's data analysis model, this research collects information from various literature sources to identify strategies that can enhance competitiveness and sustainability in the tourism sector. The findings indicate the necessity of collaboration between the government, local communities, and the private sector to optimize tourism potential and improve service quality to attract more visitors.